Allele frequency data of 20 STR loci in 2000 Korean individuals. (December 2017) - Kim, Sungmin; Park, Hyun-Chul; Kim, Jong-Sik; Nam, Younhyong; Kim, Hye Yeon; Park, Jihye; Chung, Ukhee; Lee, Jinmyung; Lim, Si-Keun; Park, Su-Jeong
Abstract: To increase the discrimination power of human identification in forensic and to evaluate expanded short tandem repeat (STR) loci, we examined a Korean sample population of 2000 unrelated individuals using both GlobalFiler™ PCR Amplification kit and PowerPlex ® Fusion System. Allele frequencies for the 20 STR loci (D3S1358, vWA, D16S539, CSF1PO, TPOX, D8S1179, D21S11, D18S51, D2S441, D19S433, TH01, FGA, D22S1045, D5S818, D13S317, D7S820, D10S1248, D1S1656, D12S391, and D2S1338) were calculated. Allele frequencies of the 20 STR loci would be useful for personal identification and paternity testing in forensics and as a standard reference database in Korea.